Efficacy, safety and Cardiovascular Disease Risk Lowering Ability of ACE Inhibitors, B-Blockers and Combination Antihypertensive Drug Regimes in Iraq - M. Sulaiman, Dlveen; J.Al-Shamma, Kassim; N.Al-Hassani, Ansam (Iraqi Journal of Pharmaceutical Sciences, 2017)
Hypertension is a major health problem throughout the world because of its high prevalence and its association with increased risk of cardiovascular diseases. It is defined as systolic blood pressure ≥ 140 mmHg and/or diastolic blood pressure ≥ 90 mmHg. The aim of this study was to compare the efficacy, safety and cardiovascular disease risk lowering ability, of three antihypertensive drug regimens. A retrospective study was carried out on 66 hypertensive patients, divided in to three groups based on their antihypertensive drug regimens (ACE inhibitors, β-blockers treated and combination antihypertensive therapy, the combination therapy consist of two or more of the following antihypertensive drugs ACE inhibitor diuretic, CCBs β-blockers), the study also included 22 healthy individuals. Duration of treatment was 2-10 years. Blood pressure and pulse rate were measured and blood sample was collected, and the serum processed for the measurement of lipid profiles, fasting blood glucose, liver function test, kidney function test, electrolytes, and C-reactive protein. Cardiovascular disease risk lowering ability have been assessed by cardiovascular risk assessor computer program. The results shows that systolic and diastolic blood pressure in the three antihypertensive drug regimens treated group, were significantly higher than systolic and diastolic blood pressure in control healthy individuals indicating that these antihypertensive drug regimens were unable to reach hypertension treatment target, although ACE inhibitors and combination antihypertensive drugs reach minimal hypertension treatment target. ACE inhibitors regimen did not show any significant adverse effects on lipid profiles and blood glucose, while β-blockers regimen adversely affected it. Most predominant adverse effects that appear, in ACE inhibitors treated group were dry cough and taste disturbances, in β-blockers treated group were bradycardia and sleep disturbances while in combination therapy treated group were according to the combination used. In combination containing thiazide diuretics, disturbed lipid profiles and hyperurecemia were predominant and in combination containing calcium channel blockers constipation and peripheral edema were predominant. Coronary heart disease and stroke risk percentage in all three antihypertensive drug regimens were significantly higher compared to control healthy individuals group, and all three antihypertensive drugs regimens have the same cardiovascular risk lowering ability. In conclusion the results indicated that all three antihypertensive drug regimens used were not efficient enough to reach hypertension treatment target, the combination therapy and ACE inhibitors regimens were only capable to reach minimal hypertension treatment target which is ≤150/90 mm Hg. Key words: ACE inhibitors, B blockers, Hypertension.